Occurrence and effects of Diplostomum sp. Infection in eyes of Acanthobrama marmid in Keban Dam Lake, Elazi?, Turkey - Dörücü, Mustafa; D?ls?z, N.; James Grabbe, M.C. (My University, 2002)
Infection with the parasite Diplostomum sp. can lead to severe ocular pathology and may result in host mortalities in commercial fish farming. Here we show that such infection is rife in a major lake used for fishing in Turkey. In a study of Acanthobrama marmid fish in Keban Dam Lake, Elazi?, Turkey, we found the infection period was normally between May and September each year, and that the prevalence and abundance of eye lens parasites reached a maximum in September. Typical results of metacercariae occurrence in the fish eye included exophthalmia, local haemorrhage and lens cataract. There was a significant positive correlation between the body condition of fish and the parasite burden (Spearman rank correlation coefficient. R=0.625, n=100, p<0.05). SDS-PAGE of solubilised insoluble proteins showed that infected lenses had an increase in high molecular weight species, suggestive of increased levels of crosslinked proteins giving rise to cataracts.
Keywords: Cataract; Exophthalmia; Fish; Lens; Parasites; SDS-PAGE